Sequential Inheritance Implementation: A Maqasid Sharia Perspective by Jasser Auda (A Case Study in Pagelaran Village, Pagelaran District, Malang Regency) - Faizah, Eka Zahrotul; Rahmawati, Erik Sabti (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The urgency of proper inheritance distribution is greatly needed in society. Therefore, an appropriate concept and legal framework are necessary in practice to ensure that the essence of justice and the objectives of Islamic law in inheritance are not compromised. This is exemplified by the practice in Pagelaran village, where inheritance is distributed not according to Islamic law, even though the majority of the population is Muslim. They have a unique method of rotating the inheritance among heirs, taking turns. This practice presents an interesting subject for analysis using the theory of maqasid shari’ah to understand the essence of the objectives behind the enactment of inheritance law in Islam. This study is empirical, using a sociological and conceptual approach. The results can be summarized in two aspects: (1) The practice of rotating inheritance in Pagelaran village is carried out alternately among heirs based on mutual agreement, and in practice, this is driven by the limited land available for distribution. It also serves as a preliminary step toward permanent land division, with the proceeds from the rotation used to cover the costs of certifying the land for each heir; (2) The practice of rotating inheritance fulfills the purpose of maqasid shari’ah as outlined by Jasser Auda and aligns with the essence of the enactment of inheritance law, ensuring the fair distribution of inheritance. This is due to the mutual agreement among the heirs, while also considering the aspects of protection and resilience within the family.